Additional Benefits of Creatine Monohydrate Supplementation on Muscle Strength, Muscle Mass Gain and Training Performance - A Systematic Review - Kuźnieców, Tadeusz; Karaban, Łukasz; Paszkowska, Monika; Mularczyk, Klaudia; Borawski, Michał; Ciuła, Aleksandra; Jakubiak, Anna; Miśkiewicz, Joanna; Znamirowska, Patrycja; Kupis, Magdalena (Quality in Sport, 2025)
Introduction: Creatine monohydrate is one of the most researched and tested supplements in sport known for its benefits on muscle strength, muscle mass gain and training performance. This systematic review synthesizes evidence from various studies to evaluate the impact of creatine monohydrate supplementation on the following outcomes. Aim of the study: To assess the effects of creatine monohydrate supplementation on muscle strength, muscle mass gain and training performance by summarizing evidence from case studies, clinical trials and long term research. State of knowledge: Studies confirm that creatine monohydrate supplementation effectively enhances athletic performance, accelerates recovery, increases muscle strength and muscle mass gain. Additionally, it offers therapeutic advantages for neurodegenerative diseases, type 2 diabetes, aging and various chronic conditions. Material and methods: A review and analysis of randomized clinical trials and clinical studies from 2017 to 2025 available in PubMed. Conclusions: Research findings indicate that long term creatine monohydrate supplementation demonstrates a positive impact on muscle strength, muscle mass gain and training performance. The evidence suggests that creatine enhances strength and hypertrophy of the muscle fibers, improves recovery, exercise capacity and high-intensity performance. These benefits make creatine monohydrate a valuable, safe and well-researched supplement for professional and amateur athletes, regardless of age and gender.